2007
DOI: 10.1016/j.bbamcr.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency activates antioxidant genes and causes DNA damage in the thyroid gland of rats and mice

Abstract: Because thyroid nodules are frequent in areas with iodine deficiency the aim of this study was to characterise molecular events during iodine deficiency that could explain mutagenesis and nodule formation. We therefore studied gene expression of catalytic enzymes prominent for H(2)O(2) detoxification and antioxidative defence, quantified DNA oxidation and damage as well as spontaneous mutation rates (SMR) in mice and rats fed an iodine controlled diet. Antioxidative enzymes such as superoxide dismutase 3, glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…1). Increased Sod3 production in rat goiter model was in line with previous murine models (Maier et al 2007), suggesting the participation of TSH in its expression in mouse and rat thyroid cells. However, analysis of patient samples did not show significant increase in SOD3 levels, which could be due to the existence of wide phenotypic variations in humans, ranging from mild to severe toxic hyperfunction of the gland.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1). Increased Sod3 production in rat goiter model was in line with previous murine models (Maier et al 2007), suggesting the participation of TSH in its expression in mouse and rat thyroid cells. However, analysis of patient samples did not show significant increase in SOD3 levels, which could be due to the existence of wide phenotypic variations in humans, ranging from mild to severe toxic hyperfunction of the gland.…”
Section: Discussionsupporting
confidence: 88%
“…Even though previous clinical analysis has demonstrated decreased total SOD activity in the plasma of Graves' disease patients (Wilson et al 1989, Abalovich et al 2003, Rybus-Kalinowska et al 2008), a recent paper suggested increased Sod3 mRNA production in thyroid caused by long-term iodine deprivation in murine models (Maier et al 2007). Since both the synthesis of autoantibodies against TSH-R in Graves' disease and the diet iodine deprivation lead to increased TSH-R signaling and consequent thyroid activation, we investigated the Sod3 expression in experimental in vivo rat goiter model (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Auto-regulation of NIS expression by iodide has previously been demonstrated (Eng et al, 1999;Glatt et al, 2005;Uyttersprot et al, 1997) and included down-regulation of NIS expression by increased iodide levels. On the other hand, NIS expression has been found to be increased by iodine deficiency, an effect that appears to occur in a TSH-independent manner (Maier et al, 2007;Scipioni et al, 2007). Thus, auto-regulatory mechanisms are likely to contribute to the regulation of NIS expression in the amphibian thyroid.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In fact, many mammalian models of thyroid goitrogenesis have used a combination of anti-thyroidal treatment and iodine deficiency (Denef, 1989). However, intracellular iodide levels are an important regulatory factor of thyroid follicular cell physiology modulating not only the effects of TSH on thyroid growth and function but affect thyroid function also in a TSHindependent manner (Eng et al, 1999;Maier et al, 2007;Scipioni et al, 2007). As a consequence, the thyroid phenotype obtained in experimental goiter studies reflects not only the over-stimulation by TSH but also thyroidal responses to altered states of iodide turnover.…”
Section: Introductionmentioning
confidence: 99%
“…In older populations, iodine deficiency impairs thyroid hormone synthesis, resulting in hypothyroidism and causing thyroid enlargement (goiter). It can also cause a compensatory increase in the cosubstrate H 2 O 2 , which in turn increases the generation of reactive oxygen species (15). A recent study by Morand et al, showed that the generation of H 2 O 2 is significantly inhibited by iodine in vivo and in vitro (16).…”
Section: Introductionmentioning
confidence: 99%